SYNERGISTIC FOUNDATIONS OF COMPUTERIZED FORECASTING IN GEOLOGY - Narseyev V.A.; Ostrovskiy E.Y. (My University, 1990)
The synergetic principle of the generation of prognostic solutions that are unaffected by stimuli was the basis for the Objective Forecast man-machine system that we developed. This system converts digital matrices of video input information into sets of basic nonspecific primitives and binary structures. All the intersections of these primitives and structures produce the necessary initial chaos from which, by means of a special evolutionary logic, there develop structures of order and metaphoric cycles. The cycles that include in their binary metaphors the object stimuli designated for forecasting are chosen as possible prognostic solutions. Any metaphor (or, more precisely, a subset of its uniform objects) that forms part of a cycle may be chosen by the expert as a prognostic solution. The use of objective forecasting for airborne geophysical prospecting and ground-based prospecting for various minerals in the USSR and certain other countries has demonstrated that it is highly effective, not only as a prospecting tool, but also as a genuine tool of scientific investigation. We emphasize in particular the great potential of Objective Forecasting in three-dimensional modeling of ore bodies during the exploration of mineral deposits.